Factors associated with patient delay among tuberculosis patients in border hospitals, Chiang Rai province, Thailand - Yotsanon Sikkhajan; Wandee Sirichokchatchawan (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The purpose of this paper is to determine the factors associated with patient delay among tuberculosis patients in border hospitals, Chiang Rai province, Thailand. Design/methodology/approach - A cross-sectional study was conducted in the four biggest border hospitals in Chiang Rai province, Thailand during May to July 2018 among 103 identified TB cases. Data were collected by a face-to-face interview with structured questionnaire on patients' general characteristics, HIV status and patient delay status. Descriptive statistics were used to analyze the patients' general characteristics, HIV and patient delay status. The association among variables and patient delay was analyzed by χ2-test. The variables with p-value<0.20 obtained in bivariate analysis were further analyzed by binary logistic regression and considered significant with p-value<0.05. Findings - All patients enrolled, most were reported with patient delay (65.0 percent). Bivariate analysis demonstrated that level of education, nationality and HIV status were associated factors for patient delay. Among these factors, binary logistic regression revealed that HIV negative TB patients were increased 6.806-fold odds of being patient delay (OR = 6.806; 95% CI: 1.174-39.462), while non-Thai TB patients were also increased 2.824-fold odds of being patient delay (OR = 2.824; 95% CI: 1.041-7.660). Originality/value - Patient delay among TB patients in Chiang Rai province was high. This study further supports the requirement on promoting of TB knowledge and awareness emphasized on non-Thai population and general public along the border areas of Chiang Rai province.